2013
DOI: 10.1002/aqc.2362
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity value of a geographically restricted soft coral species within a temperate estuary

Abstract: A threatened and uncommon soft coral species, Dendronephthya australis found in large abundance in PortStephens, within the Port Stephens-Great Lakes Marine Park (PSGLMP), New South Wales, Australia, was hypothesized to be an important habitat for many marine fishes and invertebrates, but is currently under threat from boat anchors, fishing debris entanglement and sand inundation.2. Surveys were undertaken to assess the biodiversity associated with the soft coral habitat and its adjacent habitats (sponge, seag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…The study was conducted on the southern side of the Port Stephens estuary (Figure ), which contains a range of temperate coastal and estuarine habitats (Davis, Harasti, & Smith, ; Poulos, Gallen, Davis, Booth, & Harasti, ) and a high diversity of biota (Poulos, Harasti, Gallen, & Booth, ; Smith et al., ). The entire Port Stephens estuary lies within the Port Stephens‐Great Lakes Marine Park, the largest Marine Protected Area (MPA) in New South Wales (NSW) (NSW‐MPA, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted on the southern side of the Port Stephens estuary (Figure ), which contains a range of temperate coastal and estuarine habitats (Davis, Harasti, & Smith, ; Poulos, Gallen, Davis, Booth, & Harasti, ) and a high diversity of biota (Poulos, Harasti, Gallen, & Booth, ; Smith et al., ). The entire Port Stephens estuary lies within the Port Stephens‐Great Lakes Marine Park, the largest Marine Protected Area (MPA) in New South Wales (NSW) (NSW‐MPA, ).…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted on the southern side of the Port Stephens estuary (Figure 1), which contains a range of temperate coastal and estuarine habitats Davis, Booth, & Harasti, 2015) and a high diversity of biota (Poulos, Harasti, Gallen, & Booth, 2013;Smith et al, 2010). The entire Port…”
Section: Study Areamentioning
confidence: 99%
“…data). The D. australis habitat has been found to contain high biodiversity when compared with other adjacent habitats and is considered to be an important nursery habitat for many fish species (Poulos et al, 2013). In addition to its limited distribution in Port Stephens, D. australis has only been confirmed to occur from Port Hacking (Sydney) to Port Stephens (NSW DPI, unpubl.…”
Section: H a R A S T I E T A Lmentioning
confidence: 99%
“…While adult C. auratus are found on rocky reefs across the continental slope in depths from 5 to 200 m (Curley et al, 2013;Parsons et al, 2014), juveniles are predominantly encountered within coastal embayments and estuaries (Hartill et al, 2004;Poulos et al, 2013). Acoustic telemetry studies have found that C. auratus movement patterns vary based on their size and region.…”
Section: Introductionmentioning
confidence: 99%